Supporting and Enhancing Undergraduate Learning with m-learning tools: An exploration and analysis of the potential of Mobile Phones and SMS - Jones, Geraldine; Edwards, Gabriele; Reid, Alan (Proceedings of the International Conference on Networked Learning, 2008)
New undergraduate students face a variety of challenges associated with making the transition to higher education (HE), including the removal of structures provided by the regulations and syllabus in schools and colleges, and family support. Academic demands, expositive teaching approaches, reduced interaction or personal contact with tutors, and a requirement for independent study can result in a difficult first semester for some students. The latest generation of undergraduates live and have grown up in a highly connected world which, it is claimed, causes them to develop fundamentally different ways of thinking and information processing from their predecessors. For example, today's students are thought of as inhabiting a complex array of communication networks mediated by an evolving ecology of mobile and non-mobile devices. The 'niche' occupied by the mobile phone is of particular interest owing to its prevalence across the student population and the growing functionality that they support. It is claimed that mobile learning (m-learning) opportunities can offer alternative or complementary modes of learning that more closely match these students' preferences Many pilot or demonstrator (proof of concept) m-learning projects have illuminated the potential for mobile devices to support learning and change in HE approaches. Typically these might involve the use of high specification devices running specialist software packages and/or focus on using mobile devices as part of highly student centred learning experiences located remote from more traditional learning contexts. Few studies have explored how to harness existing infrastructures of personal mobile devices or the protocols of social communication for academic purposes. Furthermore, little is known about how mobile mediated communication might compliment more traditional learning and teaching contexts (e.g. lectures, seminars and more recently and increasingly, Virtual Learning Environments (VLEs)). This paper seeks to add knowledge in these areas by reporting and reflecting on a case study which investigates how the academic and personal development of first year students (n=81) on an undergraduate sports education degree can be supported and enhanced by m-learning. Drawing on Moore's theory of transactional distance we aimed to reduced the 'distance' between tutor and students and students and the course content. More specifically, by structuring inter-session study time using group learning activities we sought to establish learning networks that more effectively support the student experience on a core unit of study. In addition, we sought to harness the communication cultures and skills of these 'digital native'students, using mobile phones and SMS. We review findings from a student survey about the extent of mobile phone ownership, the capability of the devices, the range of contracts, and student views about the potential use of their phones as tools for learning. The survey informed the initial design of a set of group learning activities giving structure to out-of-session study while facilitating greater connectivity between the students and their course, and between the students and the tutor. Asynchronous tools (forums and wikis) in the VLE were used in concert with mobile communication, managed through a bulk texting service. We report on the outcomes of our formative and summative evaluations which yielded both qualitative and quantitative data from a variety of sources: focus groups, an online discussion forum, student questionnaire, access statistics from the Moodle VLE and bulktexting service, and the tutor's reflective journal. We discuss our early findings linked to the outcomes of our evaluation, specifically three key issues: how texting can support student time management; how the SMS communication can extend the tutor's voice; and to what extent we were successful in appropriating students' personal mobile communication infrastructures. Finally we discuss how this study addresses some of the challenges associated with the perceived increase in transactional distance caused by physical, cognitive and digital remoteness between students and their teachers.